Porosity Analysis of Pliocene Limestone from the Mundu Formation Based on Core and Petrographic Analysis - Muh Ferdian Yusuf; Siti Umiyatun Choiriah; Wahyuni Annisa Humairoh; Samuel Antonio Gutteres; Kharisma Idea; Danang Faisal Amri (Jurnal Penelitian Pendidikan IPA, 2025)
This study analyzes the porosity characteristics of Pliocene limestone from the Mundu Formation in the Gunung Pegat area, Lamongan, East Java, which lies within the Rembang Zone and is considered a potential carbonate reservoir. The research involved geological field mapping, measurement of four stratigraphic profiles, and collection of thirteen rock samples. Laboratory methods included petrographic analysis to classify lithofacies, core analysis to determine porosity, calcimetry for carbonate content, and microfossil analysis for age and depositional environment. Petrographic results show dominant packstone and wackestone lithologies, with pore types consisting of interparticle, moldic, and vuggy pores formed through bioclast dissolution and diagenesis. Core analysis reveals porosity values ranging from 1.5% to 22.1%, averaging 13.6%. High-porosity zones (>20%) occur in the western and northwestern parts, associated with bioclast-rich facies and meteoric water dissolution, whereas low values (<10%) are concentrated in the southeastern part due to compaction and recrystallization. These findings indicate that lithofacies variation and diagenetic processes significantly control reservoir quality. Overall, the Mundu Formation demonstrates good potential as a carbonate reservoir, particularly within packstone facies with well-developed secondary porosity, providing a useful basis for hydrocarbon and groundwater exploration in the northern East Java Basin.